Renal expression of PLA2R, THSD7A, and IgG4 in patients with membranous nephropathy and correlation with clinical findings. Issue 4 (13th December 2020) - Kaya, Bulent; Paydas, Saime; Balal, Mustafa; Eren Erdogan, Kivilcim; Gonlusen, Gulfiliz
Abstract: Background: Membranous nephropathy (MN) is the most common cause of nephrotic syndrome in nondiabetic adults. M‐type phospholipase A2 receptor (PLA2R), thrombospondin type‐1 domain‐containing 7A (THSD7A) are known as target podocyte antigens in membranous nephropathy (MN). Antibodies against these podocyte antigens are used in the initiation of treatment and response monitoring. However, the relationship between renal podocyte antigens and treatment response is not clear yet. We evaluated the relationship between immunohistochemical PLA2R, THSD7A and IgG4 staining, clinical findings and treatment response in kidney biopsies. Methods: Fifty‐eight patients with MN were included in this retrospective study. In the renal biopsy samples of the patients, PLA2R, THSD7A and IgG4 were stained immunohistochemically and evaluated by light microscopy. The clinical, laboratory and treatment results of the patients were obtained from the hospital records. Results: The study included a total of 58 patients with MN and a mean follow‐up period of 32.3 ± 19.7 months. In patients with primary MN; PLA2R, THSD7A and IgG4 were positive in 57.1% (n = 28), 12.2% (n = 6) and 69.4% (n = 34), respectively. Only PLA2R staining was distinctly higher in patients with primary MN than secondary MN ( P = .025). Dual positivity (PLA2R + THSD7A) was detected in five (10.2%) of patients with primary MN. We did not determine any relationship between the PLA2R, THSD7A and IgG4 staining patterns and treatment response of the patients. Conclusion: It was found no correlation between PLA2R, THSD7A and IgG4 staining in kidney tissue and treatment response. Interestingly, dual positivity (PLA2R + THSD7A) was detected only in primary MN.